Targeting innate immunity for neurodegenerative disorders of the central nervous system. Issue 5 (September 2016) - Andreasson, Katrin I.; Bachstetter, Adam D.; Colonna, Marco; Ginhoux, Florent; Holmes, Clive; Lamb, Bruce; Landreth, Gary; Lee, Daniel C.; Low, Donovan; Lynch, Marina A.; Monsonego, Alon; O'Banion, M. Kerry; et al.
Abstract: Neuroinflammation is critically involved in numerous neurodegenerative diseases, and key signaling steps of innate immune activation hence represent promising therapeutic targets. This mini review series originated from the 4th Venusberg Meeting on Neuroinflammation held in Bonn, Germany, 7–9th May 2015, presenting updates on innate immunity in acute brain injury and chronic neurodegenerative disorders, such as traumatic brain injury and Alzheimer disease, on the role of astrocytes and microglia, as well as technical developments that may help elucidate neuroinflammatory mechanisms and establish clinical relevance. In this meeting report, a brief overview of physiological and pathological microglia morphology is followed by a synopsis on PGE2 receptors, insights into the role of arginine metabolism and further relevant aspects of neuroinflammation in various clinical settings, and concluded by a presentation of technical challenges and solutions when working with microglia and astrocyte cultures. Microglial ontogeny and induced pluripotent stem cell‐derived microglia, advances of TREM2 signaling, and the cytokine paradox in Alzheimer's disease are further contributions to this article. Neuroinflammation is critically involved in numerous neurodegenerative diseases, and key signaling steps of innate immune activation hence represent promising therapeutic targets. This mini review series originated from the 4th Venusberg Meeting on Neuroinflammation held in Bonn, Germany, 7–9th May 2015, presenting updates on innate immunity in acute brain injury and chronic neurodegenerative disorders, such as traumatic brain injury and Alzheimer's disease, on the role of astrocytes and microglia, as well as technical developments that may help elucidate neuroinflammatory mechanisms and establish clinical relevance. In this meeting report, a brief overview on physiological and pathological microglia morphology is followed by a synopsis on PGE2 receptors, insights into the role of arginine metabolism and further relevant aspects of neuroinflammation in various clinical settings, and concluded by a presentation of technical challenges and solutions when working with microglia cultures. Microglial ontogeny and induced pluripotent stem cell‐derived microglia, advances of TREM2 signaling, and the cytokine paradox in Alzheimer's disease are further contributions to this article. Abstract : Neuroinflammation is critically involved in numerous neurodegenerative diseases, and key signaling steps of innate immune activation hence represent promising therapeutic targets. This mini review series originated from the 4th Venusberg Meeting on Neuroinflammation held in Bonn, Germany, 7–9th May 2015, presenting updates on innate immunity in acute brain injury and chronic neurodegenerative disorders, such as traumatic brain injury and Alzheimer's disease, on the role of astrocytes and microglia, as well as technical developments that may help elucidate neuroinflammatory mechanisms and establish clinical relevance. In this meeting report, a brief overview on physiological and pathological microglia morphology is followed by a synopsis on PGE2 receptors, insights into the role of arginine metabolism and further relevant aspects of neuroinflammation in various clinical settings, and concluded by a presentation of technical challenges and solutions when working with microglia cultures. Microglial ontogeny and induced pluripotent stem cell‐derived microglia, advances of TREM2 signaling, and the cytokine paradox in Alzheimer's disease are further contributions to this article.